ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN DAN KINERJA KARYAWAN BPR DI SULAWESI SELATAN - Mashur Razak (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
This research aims to know (1) the effect of leader personal characteristic toward work satisfaction, work motivation and perfromance of employee both direct or indirect; (2) the effect of leader individual competention toward work satisfaction, work motivation and performance of employee both direct or indirect; (3) the effect of leadership attitude toward work satisfaction, work motivation, and performance of employee both direct or indirect ; (4) the effect of communication capability toward work satisfaction, work motivation and performance of employee both direct or indirect; (5) the effect of work satisfaction toward work motivation and performance of employee both direct or indirect; and (6) the effect of work motivation toward performance of employee of BPR in South Sulawesi. Data used in this research are primary data which collected by 220 person taken as samples. The data collected were then analyzed by confirmatory factor and model verification by using structural equation modeling (SEM) analysis, and the results were then justified. The Result of the research showed that: (1) The personal characteristic has positive effect and significant influence toward the work employee satisfaction and motivation, but it was not significant to employee performance, (2) The individual competency of leader has positive effect and significant toward the satisfaction, motivation work and performance of employee, (3) The leadership attitude has positive effect and significant influence toward the satisfaction, motivation work and performance of employee, (4) The communication ability of leader has positive effect and significant toward the work satisfaction, motivation and performance of employee, (5) The motivation work has positive effect and significant toward the employee performance of Bank Perkreditan Rakyat (BPR) in South Sulawesi.